2015
DOI: 10.3346/jkms.2015.30.10.1490
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of the Suicide Attempters Who Refused to Participate in a Suicide Prevention Case Management Program

Abstract: Case management interventions for suicide attempters aimed at helping adjust their social life to prevent reattempts have high nonparticipation and dropout rates. We analyzed the clinical characteristics of the group who refused to participate in the suicide prevention program in Korea. A total of 489 patients with a suicide attempt who visited Uijeongbu St. Mary's Hospital, the Catholic University of Korea, from December 2009 to December 2013 were analyzed. All patients were divided into the participation gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…In the western parts of the world, marriage is considered as a protective factor, but in Bangladesh repeated articles reported the reverse phenomenon [ 1 , 5 8 ], which can be explained by socioeconomic structure of this specific area. Hanging was found to be the commonest method of suicide, 223 (82.29%) ( Table 2 ); the finding correlates with other global findings [ 1 , 9 , 10 ]. Previous review revealed larger proportion of suicides caused by poisoning [ 1 , 11 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the western parts of the world, marriage is considered as a protective factor, but in Bangladesh repeated articles reported the reverse phenomenon [ 1 , 5 8 ], which can be explained by socioeconomic structure of this specific area. Hanging was found to be the commonest method of suicide, 223 (82.29%) ( Table 2 ); the finding correlates with other global findings [ 1 , 9 , 10 ]. Previous review revealed larger proportion of suicides caused by poisoning [ 1 , 11 ].…”
Section: Discussionsupporting
confidence: 79%
“…Suicide happens because of multifactorial involvement such as genetic, psychological, social, and cultural risk factors; those can interact in different perspectives such as diathesis-stress model and gene-environment interaction [ 3 ]. Psychiatric morbidities play an important role in suicide as previous research mentioned that about 90% of suicide victims were found to have at least one psychiatric disorder and depression was the most mentionable one [ 9 , 10 ]. In Bangladesh, previous studies found variations in risk factors and psychological autopsy is still yet to be conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Suicidality is a complex behaviour with numerous predisposing factors (Isometsä, 2014) especially mental disorders. Over ninety percent of suicides are committed by individuals with mental disorders, especially depression (Park et al, 2015;Gunnell & Lewis, 2005;Shibre et al, 2014). There is a paucity of evidence regarding suicidality in Nigeria among persons with mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…5,9,11,13,16,17,22,35,37 Other psychiatric disorders found in psychological autopsies of suicidal deaths are personality disorders, 16 adjustment disorder, 35 alcohol and drug related disorders, 11,16,17,35 bipolar disorders, 22,35 schizophrenia and other psychotic disorder, 16,35 anxiety disorders, 35 impulse control disorders, 35 somatoform disorders, 35 sleep disorders, 35 eating disorders, 35 and childhood psychiatric disorders. 35 Other risk factors can be accounted as availability of lethal means, psychiatric services availability, attitude to suicide, help seeking behaviors, comorbid physical illness and other social factors. 17 Previous study revealed that up to 83% of committed suicides have had contacts with primary care physicians within a year and two third of them within a month.…”
Section: Psychiatric Morbidities and Suicidementioning
confidence: 99%
“…5,14 Befriending approach is used in most of the hotline centres and unguided brief mobile intervention, telephone after care interventions delay and reduce suicide significantly. [4][5][6]17,34,35 Moreover, totline services are approachable even in emergencies and can account earlier support than long waiting list. 6 As well as reducing the suicidality the hotline interventions has a positive impact on the psychosocial aspects such as reduction of depressive symptoms, hospital admissions and health services resource utilization.…”
Section: Hotline Interventionsmentioning
confidence: 99%